A New Double Stranded RNA Suppresses Bladder Cancer Development by Upregulating p21Waf1/CIP1 Expression. (30th March 2015) - Wang, Chenghe; Ge, Qiangqiang; Chen, Zhong; Hu, Jia; Li, Fan; Song, Xiaodong; Xu, Hua; Ye, Zhangqun
Abstract : We have previously demonstrated that miR-1180-5p has potent ability to upregulate p21 expression by targeting promoter and inhibit bladder cancer. This prompted us to conjecture that a candidate dsRNA (dsP21-397) with perfect complementarity to the miR-1180-5p target site of p21 promoter may also trigger p21 expression. Transfection of dsP21-397 into T24 and EJ cells significantly activated p21 expression at 72 h and the activation presented in a time-course and dose-dependent manner. Moreover, the p21-activated activities of dsP21-397 and miR-1180-5p are not significantly different. Overexpression of p21 downregulated Cyclin D1, CDK4/6, and Cyclin A2 expression, and thereby induced cell cycle arrest and inhibited proliferation. Moreover, dsP21-397 suppressed bladder cancer largely depended on manipulating p21. In conclusion, our study identifies a pair of miRNA-dsRNA mediating endogenous p21 overexpression.